Characteristics and Control of Pear Scab (Venturia nashicola): A Review - Eu Ddeum Choi; Janghoon Song; Ho-Jin Seo (Research in Plant Disease, 2023)
Pear scab, caused by Venturia nashicola, is one of the most devastating diseases of Asian pears in Korea, Japan, China, and Taiwan. To manage this disease, growers mainly relied on chemical control. However, continuous use of chemical causes not only environmental contaminant but also the emergence of resistance to pathogens, so a more sustainable management plan is needed. Therefore, it is necessary to understand the life cycle and infection characteristics of V. nashicola and to set an active control strategy according to meteorological conditions rather than, as in the past, calendar-based control or continuous use of a specific fungicide system. Various results of the related research results were reviewed to summarize the race, infection characteristics, and control system of V. nashicola, a pear scab, and to discuss plans for a more effective control system.